Avaliação da cultura de segurança do paciente em cinco hospitais brasileiros: comparação por categoria profissional - Vale, Victor César de Souza (2024)
Introduction: Safety culture is the product of individual and collective values, attitudes, perceptions, and competencies, whose outcome determines an institution's commitment and style. Objective: To analyze and compare patient safety culture in five Brazilian hospitals belonging to the same management organization, from the perspective of different healthcare professional categories. Materials and Methods: A cross-sectional study using the Hospital Survey on Patient Safety Culture (HSOPSC) instrument. The instrument was digitized and sent to the email addresses of professionals stationed in five Brazilian hospitals. Percentages of positive, neutral, and negative responses were calculated to identify strong and weak areas for the institutions' safety culture. Results: 360 questionnaires were analyzed, and considering the overall results, the general percentage of positive responses was 51.64%. The dimension with the highest percentage of positive responses was Organizational Learning – Continuous Improvement (with 71.21%), and the one with the lowest performance was Non-punitive Response to Error (with 26.19%). When comparing professional categories, the group composed of Physiotherapists, Occupational Therapists, and Speech Therapists had the highest percentage of positive responses (58.32%), while the group of Physicians obtained the lowest (45.40%). Conclusion: The results show that, despite being under the coordination of the same funding and regulatory entity, the evaluated institutions do not exhibit uniformity regarding patient safety culture, as evidenced by the perceptions of different professional categories. This suggests the existence of microcultures and underscores the need for standardization of processes, protocols, and tools that encompass and involve all units and professional categories. The results also highlight the need to encourage, promote, and disseminate a fair culture in those units.